Postgraduate Students’ Strategies in Reading Journal Articles for Thesis Writing: A Qualitative Study - Inaya Hasanah Rahman; Andi Nur Annisa; Nur Ilma Putri Fachruddin (Universitas Islam Negeri Palopo, 2026)
Reading journal articles is a central yet challenging activity for postgraduate students engaged in thesis writing. This study aims to explore how postgraduate students approach academic reading, the strategies they employ at different stages of thesis writing, the reasons underlying their strategic choices, and the challenges they encounter along with their adaptive responses. Grounded in metacognitive theory, sociocultural theory, and the academic emotions framework, this study adopts a qualitative multiple-case study design within an interpretivist paradigm. Six postgraduate students from an English Education program at a state university in Indonesia were purposively selected. Data were collected through semi-structured interviews, document-based stimulated recall, and reflective reading logs, and analyzed using thematic analysis. The findings reveal that postgraduate students engage in active and critical reading practices characterized by evaluation, questioning, and selective engagement with texts. Reading strategies are found to be dynamic and stage-dependent, shifting from exploratory approaches during the proposal stage to more focused and analytical strategies in the literature review and methodology stages. Participants demonstrate strong metacognitive awareness by planning, monitoring, and evaluating their comprehension while flexibly adapting strategies to meet specific academic purposes. Despite these competencies, students face challenges related to complex academic language, dense theoretical content, and information overload. These challenges, however, stimulate strategic adaptation, including selective reading, systematic organization of information, and the use of social and technological support. This study contributes to the understanding of postgraduate academic reading as a complex, situated, and adaptive practice shaped by cognitive, social, and emotional factors, and offers pedagogical implications for supporting strategic reading development in English Language Teaching contexts.